The Potential of Indonesia's Ship Engine Market to Attract Foreign Investors for Domestic Manufacturing - Andi Komara; Kevin Theodore Putra Iroth; Sungkono Sungkono; John Samuel Saragih; Sarifah Ulfa Sahubawa; Maulina Dwiwanti (Equity: Jurnal Ekonomi, 2024)
Indonesia is a prospective country for everyone to decide on an investment. There are four reasons to strengthen the motivation to invest some capital in the maritime industry sector. Moreover, Indonesia has approximately 342 shipbuilding companies and 127 ship component companies which spread out throughout the nation. However, Indonesia has no engine maker company yet and this is an opportunity for all investors who want to establish their own engine company or a branch in this country. The biggest opportunity is in the fishery sector with a growing number of fishing vessels and the Indonesian marine fishery production potential as the largest archipelagic country is still increasing. Furthermore, other opportunities are passenger ships, cargo ships, and tug boats because they have a significant number in the nation. In addition, Indonesia also gives several incentives to new investors, like a tax allowance, a super tax deduction, and an import duty facility. Ultimately, the prospect has been considered to involve responsibilities among shipowners, shipyards, main engine manufacturers, and the government.